DAMPAK AWAL KRISIS EKONOMI 1998 TERHADAP TINGKAT PENDAPATAN TENAGA KERJA (Pendekatan Social Accounting Matrix SAM dan Structural Path Analysis SPA) - Widodo, Wahyu (Universitas Muhammadiyah Magelang, 2007)
The research attempts to analyze the initial impact of the economic crisis to the wages rate. The crisis that occurred first time in the mid of July 1997 is signaled by the faltof rupiah currency then broaden and become a multi dimensions crisis. Finally, it caused serious impact to both macroeconomic and microeconomic, and as a reesult, the national economy falls into the worst condition after the remarkeable achievement in the early 1990. The facts show that economic growth is decreased up to 13 percent in 1998, while unemployment rate increased from 4.7 percent in 1997 to 5.5 percent in 1998. In line with that, real wages also decreased approximately 30 40 percent during the same period. Two approaches are used in this research to analyze the futher impacts. First, using the multiplier decomposition of Social Accounting Matrix (SAM) and secondly, using the Structural Path Analysis (SPA) based on the SAM multiplier decomposition. In this research, the economic crisis is estimated by the contaction rate of eachsector during 1998. The research found several important results i.e. 1). Among the labor categories, the clerical labor received the hardest impact of crisis compared to the manual, agricuture and manager labor. 2). In general, labor at urban area hit moreimpact compared the labor atrural area,expect for the agriculture sector; 3). Manufacturing industries give the major contribution tothe decline of wage rate compared to other sectors; 4). The Structural Path Analysis (SPA) show that the decline of wage rate is mainly caused by the contraction of the sector to which th elabor worked; 5). The SPA also show that the chemical, fertilizer, clay products and basics metal industries are the sectors which give the largest contribution to the decline of wage rage particularly along its path.